One Year of COVID-19 in Pregnancy: A National Wide Collaborative Study - Borges Charepe, Nadia (2022)
Introduction: Even though the risk of COVID-19 in pregnancy may be increased, large-scale studies are needed to better understand the impact of the infection in this population. The aim of this study is to describe obstetric complications and the rate of vertical transmission in pregnant women with SARS-CoV-2 infection.Material and Methods: Detected cases of SARS-CoV-2 infection in pregnancy were registered in Portuguese hospitals by obstetricians. Epidemiological, pregnancy and childbirth data were collected.Results: There were 630 positive cases in 23 Portuguese maternity hospitals, most at term (87.9%) and asymptomatic (62.9%). The most frequent maternal comorbidity was obesity. The rates of preterm birth and small-to-gestational-age were 12.1% and 9.9%, respectively. In the third trimester, 2.9% of pregnant women required respiratory support. There were eight cases (1.5%) of fetal death, including two cases of vertical transmission. There were five cases of postpartum respiratory degradation, but no maternal deaths were recorded. The caesarean section rate was higher in the first than in the second wave (68.5% vs 31.5%). RT-PCR SARS-CoV-2 positivity among newborns was 1.3%.Conclusion: SARS-Cov-2 infection in pregnancy may carry increased risks for both pregnant women and the fetuses. Individualized surveillance and the prophylaxis of this population with vaccination. is recommended in these cases.